Powtoon Interactive Media with a Problem Based Learning Model on Student Learning Outcomes and Interests in Plane figure - Asmaniah, Tansa Giri; wati, Rusnila (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
The lack of appropriate use of models, methods, strategies and media applied by teachers is the background of this research. Based on field studies, this happened to fourth-grade students at Mentari Elementary School, which is an elementary school in Kartasura District. There are several learning media whose use is not maximized so that automatic learning will be more teacher-centered. This can result in low student learning outcomes and interest. This study aims to determine the effect of Powtoon interactive media with the Problem Based Learning model on the learning outcomes and interest of fourth grade students in elementary school plane figure material. The method used in this study was a quasi-experimental design with a Control Group Pretest and Posttest Design. The Cluster Random Sampling technique is used as a sampling technique. Data collection techniques in this study through observation, tests, questionnaires and documentation. Data analysis techniques used include normality test, homogeneity, t test and ANOVA test. From the research results it was found that the t-test showed the value of Sig. (2-tailed) <0.05 and the ANOVA test shows a Sig. 0.008 <0.05, it can be concluded that Ho is rejected and Ha is accepted. Therefore, there is an influence of Powtoon interactive media with the Problem Based Learning model on student learning outcomes and interest in plane figure material at Mentari Elementary School.